The Friedrich Ebert Foundation and the Spanish Socialists during the Transition to Democracy, 1975-1982 - Muñoz Sanchez, Antonio (2016)
This article explores the activities of the Friedrich Ebert Foundation in Spain during the transition to democracy. It describes the financial, logistical and training support with which this German Foundation contributed to the unexpected rebirth of the Spanish Socialist Party after Franco and its meteoric emergence as the leading left-wing party. It also assesses its cooperation with the Socialist trade union, which moved from irrelevance to a position of importance greater than the powerful Communist union. Finally, the article examines how the Foundation diversified its activities in order to meet the growing needs of and challenges faced by the Spanish Socialists in their path towards power.